Glomerular protein sieving and implications for renal failure in Fanconi syndrome. - Norden, A; Lapsley, M; Lee, P; Pusey, C; Scheinman, S; Tam, F; Thakker, R; Unwin, R; Wrong, O (2001)
BACKGROUND: Glomerular sieving coefficients (GSCs) of proteins have been measured extensively in animals but not humans. We have studied the proteinuria of Fanconi syndrome, a "knock-out" of renal tubular protein reabsorption, to estimate GSCs and detect potential contributors to development of renal failure. METHODS: Immunoassay of proteins and polypeptides in serum and urine of patients with early Dent's disease (mean GFR = 83 mL/min, range 60 to 101, N = 5), Lowe's syndrome (N = 3), and ADIF (N = 2) were used. RESULTS: Twenty-one proteins, ranging in mass from insulin (5.1 kD) and parathyroid hormone (PTH; 9.4 kD) to transferrin (78 kD) and intact IgG (160 kD), were present in Fanconi urine at> 6 to 1000-fold normal. A simple model assuming complete "knock-out" of the reuptake of each protein filtered normally by the glomerulus was applied to protein excretion by Dent's patients. GSCs were estimated for 12 plasma proteins, including albumin (7.7 +/- 0.9 x 10-5) and IgG (4.2 +/- 0.28 x 10-5; mean +/- SEM). We calculated the albumin concentration in normal glomerular filtrate to be 3.5 +/- 0.41 mg/L (53 +/- 6.4 nmol/L), consistent with studies in rat and dog. CONCLUSIONS: To our knowledge, this study provides the first estimates of human in vivo GSCs. Our model explains why tubular proteinuria of Fanconi syndrome includes proteins of mass of albumin and above as well as low-molecular-weight proteins, and further characterizes the endocytic pathway(s) believed defective in these syndromes. High urinary concentrations of potentially bioactive hormones such as PTH, insulin, IGF-1 and the chemokine monocyte chemoattractant protein-1 (MCP-1), were found; their presence in tubular fluid may contribute to the hypercalciuria, interstitial fibrosis, and the progressive renal failure of Fanconi syndromes.